PENGARUH TRANSFORMASI TEKNOLOGI FINANSIAL TERHADAP TRANSPARANSI PELAPORAN KEUANGAN: (STUDI BANK KONVENSIONAL BEI 2022-2024) - Hana Salsabila; Khoirul Fatah (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: Financial technology transformation has become one of the main drivers of digitalization in the banking sector and is expected to enhance financial reporting transparency. This study aims to examine the effect of financial technology transformation on financial reporting transparency in conventional banks listed on the Indonesia Stock Exchange during the 2022–2024 period. Methods: This study employs a quantitative explanatory approach using secondary data obtained from annual reports and financial statements. The sample consists of 19 conventional banks selected through purposive sampling, resulting in 57 observations. The data were analyzed using panel data regression. Results: The findings indicate that financial technology transformation does not have a significant effect on financial reporting transparency at the 5% significance level. The results suggest that banking digitalization during the study period was primarily aimed at improving operational efficiency and customer service rather than strengthening the quality of public information disclosure. In addition, financial reporting transparency appears to be influenced by other factors, such as corporate governance, disclosure policies, and regulatory compliance. Conclusion and suggestion: This study concludes that financial technology transformation has not yet become a primary determinant of financial reporting transparency in conventional banks in Indonesia. Future research is recommended to include additional explanatory variables and extend the observation period to provide a more comprehensive understanding of the factors affecting financial reporting transparency. Keywords: Conventional Banking, Corporate Governance, Financial Reporting Transparency, Financial Technology Transformation, Indonesia Stock Exchange